A comprehensive review of deep brain stimulation for Parkinson's disease: The history, current state of the art and future possibilities - Avery Foote; Emma de Waal; Frederico Caiado; Amr Samman; Arkadiy Ukolov (Medicine in Novel Technology and Devices)
Parkinson's Disease (PD) is a neurodegenerative condition that results in the death of dopamine-producing neurons that mainly affects the motor cortex and causes such symptoms as tremors and difficulty speaking. White early treatments for PD included ablative and stereotactic surgeries, the precise destruction of specific brain structures, these lost favor with the emergence of levodopa in the second half of the 20th century. Nevertheless, the shortcomings of this drug, such as the reduced patient sensitivity to the treatment, sparked a new interest in surgical procedures, which in turn gave rise to the Deep Brain Stimulation (DBS) technology. In this paper, we explore the history of PD treatments with a focus on DBS, as well as the developments and advancements of the technology, including innovations in software, hardware and targeting techniques. We highlight the state of the art of PD treatment and outline future possibilities in this field.